ATTITUDES TOWARDS MENTAL ILLNESS TO DECREASE THE FAMILY CAREGIVERS’ BURDEN - Faida Annisa; Agus Sulistyowati; Dini Prastyo Wijayanti (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Community-based mental health services should be aware of the role of family and society. With the stigma issues in mental illness that still remain, the impact would be greater on the family caregivers. Their behavior toward patients creates a burden on care. Objectives: Assess the relationship between attitude toward mental illness and burden of family caregivers. Methods: Descriptive with a cross sectional approach. There were 120 family caregivers of patients with Schizophrenia in the hospital in Surabaya, Indonesia participated on this study by using purposive sampling technique. The instruments on this study were Attitudes towards Schizophrenia Questionnaire (ATSQ) and Burden Assessment Schedule (BAS). Results: The higher burden correlates with the negative attitude toward mental illness (r(118)= .54, p= .000). Conclusion: Realistic attitude would relieve the burden for family caregiver. Therefore, need more knowledge for family and society to shape their behavior toward patients with mental illness.